Self-repairing multifunctional polysulfide composite membrane and preparation method and application thereof
Patent Information
- Application Number
- CN202611319248.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-23
AI Technical Summary
然而,现有的芳砜纶膜存在如下问题:(1)由于存在各向异性导致芳砜纶膜横向拉伸强度较低;(2)使用过程中会由于不可避免地受到刮擦、冲击或疲劳应力而产生微裂纹
[0020]为了实现上述发明目的,本发明还提供一种上述任一种自修复多功能芳砜纶复合膜或根据上述任一制备方法制得的自修复多功能芳砜纶复合膜的应用,适用于航空航天、柔性电子、特种防护任一技术领域。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of multifunctional polymer composite membrane material technology, specifically relating to an aramid fiber composite membrane with small difference in longitudinal and transverse tensile strength, self-healing properties, strong interlayer bonding, and excellent high-temperature resistance, and its preparation method. Background Technology
[0002] Aryl sulfone is a special engineering polymer that is resistant to high temperatures, flame retardant, and insulating. Its films are of strategic significance in aerospace, flexible electronics, and special protection fields. However, existing aramid films have the following problems: (1) Due to anisotropy, the transverse tensile strength of aramid films is low; (2) During use, microcracks will inevitably be generated due to scratches, impacts, or fatigue stress. These microcracks are usually difficult to detect, but they will become stress concentration points. Under continuous load or environmental action, they will continue to expand and eventually cause the overall fracture of the material, resulting in equipment failure or protection failure. Imparting self-healing function to aramid films can improve their service life. (3) The interlayer bonding force is weak, and delamination failure is easy to occur during use.
[0003] Therefore, there is an urgent need to develop an aramid fiber membrane and its preparation method that can improve the difference in longitudinal and transverse tensile strength and interlayer bonding force, while having efficient and reliable self-healing capabilities. Summary of the Invention
[0004] In order to overcome the defects of the prior art, the present invention aims to: (1) provide a multifunctional aramid fiber composite membrane with small difference in longitudinal and transverse tensile strength, strong interlayer bonding force, and high reversible self-healing properties; (2) provide a method for preparing the above-mentioned multifunctional self-healing aramid fiber composite membrane; and (3) provide applications of the above-mentioned aramid fiber composite membrane.
[0005] To achieve the above-mentioned objectives, this invention provides a self-healing multifunctional aramid fiber composite membrane. The composite membrane is formed by a spin-coating process using a composite casting solution prepared from aramid fiber resin dissolved or dispersed in N-methylpyrrolidone, ultra-high molecular weight aramid fiber, amino-modified graphene oxide, and a self-healing dynamic network prepolymer to form an orthogonal stacked structure. The composite membrane comprises a bicontinuous phase formed by the self-healing dynamic network prepolymer and a rigid aramid fiber main network, and a dispersed phase reinforced with amino-modified graphene oxide and ultra-high molecular weight aramid fiber. The composite membrane has a longitudinal-to-transverse strength ratio ≥0.91, an interlayer peel strength ≥7.9 N / cm, and a transverse tensile strength repair efficiency ≥93% after the first repair.
[0006] Furthermore, in the self-healing multifunctional aramid fiber composite membrane provided by this invention, the rigid aramid fiber main network in the dual continuous phase serves as the high-temperature resistant skeleton of the composite membrane and undertakes the main load-bearing function; the self-healing dynamic network prepolymer is a furan-maleimide dynamic covalent network, which runs through the rigid aramid fiber main network. Through temperature-controlled reversible covalent bond breaking and recombination, the composite membrane is endowed with self-healing ability: the above composite membrane repair process can be repeated at least 5 times, and the transverse tensile strength repair efficiency after the 5th repair is not less than 90%.
[0007] Furthermore, in the self-healing multifunctional aramid composite membrane provided by the present invention, the self-healing dynamic network prepolymer is prepared by reacting furan-terminated polyamide with 4,4'-diphenylmethane bismaleimide in a molar ratio of furan group to maleimide group of (1.02~1.10):1; the mass ratio of self-healing dynamic network prepolymer to aramid resin is (20:80)~(35:65).
[0008] To achieve the above-mentioned objectives, the present invention also provides a method for preparing any of the above-mentioned self-healing multifunctional aramid fiber composite films, comprising the following steps:
[0009] S1. Synthesis of self-healing dynamic network prepolymer: First, furan-terminated polyamide oligomers are synthesized; then, furan-terminated polyamide oligomers and 4,4'-diphenylmethane bismaleimide are dissolved in N-methylpyrrolidone to prepare a solution with a solid content of 25wt%~35wt%, and the self-healing dynamic network prepolymer solution is obtained after the reaction.
[0010] S2. Preparation of composite casting solution: Aramid sulfone resin and ultra-high molecular weight aramid sulfone are dissolved in N-methylpyrrolidone to prepare a main solution with a solid content of 16wt%~20wt%; amino-modified graphene oxide is ultrasonically dispersed in N-methylpyrrolidone to obtain a dispersion; the dispersion and the main solution are mixed evenly and then added to the dynamic network prepolymer solution obtained in step S1. Solvent is added to adjust the total solid content. After vacuum degassing and filtration, a uniform and stable composite casting solution is obtained.
[0011] S3. Spin coating to prepare a multilayer structure: The casting solution is coated along the first direction on a preheated smooth substrate to obtain a first gel layer; the substrate carrying the first gel layer is rotated 90 degrees and coated along the second direction perpendicular to the first direction to obtain a wet film with a multilayer structure.
[0012] S4. Graded curing and molding: Under inert gas protection, the wet film is first kept at 105~115℃ for 80~100 minutes; then the temperature is gradually increased to 150~170℃ and kept for 20~40 minutes; then the temperature is further increased to 180~200℃ and kept for 20~40 minutes; after curing, the substrate is cooled and peeled off to obtain the self-healing multifunctional aramid composite film.
[0013] Furthermore, in the method for preparing a self-healing multifunctional aramid composite membrane provided by the present invention, in step S1, the furan-terminated polyamide oligomer and the 4,4'-diphenylmethane bismaleimide furan group to maleimide group are prepared in a molar ratio of (1.02~1.10):1.
[0014] Furthermore, in the method for preparing a self-healing multifunctional aramid composite membrane provided by this invention, in step S1, the synthesis of furan-terminated polyamide oligomers includes the following steps:
[0015] (1) Add adipic acid chloride, hexamethylenediamine and furanylmethylamine to NMP solvent in a molar ratio of 4:3:2, and add triethylamine in an equal molar amount to adipic acid chloride as an acid-binding agent. Stir the reaction under ice-water bath conditions of 0~5℃.
[0016] (2) After the reaction is complete, the reaction solution is poured into deionized water to precipitate, and then washed with deionized water and anhydrous ethanol in sequence. After vacuum drying, the product is obtained.
[0017] Furthermore, in the method for preparing a self-healing multifunctional aramid fiber composite membrane provided by the present invention, in step S1, the self-healing dynamic network prepolymer reaction is a solution with a solid content of 25%~35% reacting at 60~70°C for 40~60 minutes.
[0018] Furthermore, in the method for preparing a self-healing multifunctional aramid composite membrane provided by the present invention, the mass ratio of the self-healing dynamic network prepolymer solid to the aramid resin in the composite casting solution is (20:80) to (35:65).
[0019] Furthermore, in the method for preparing a self-healing multifunctional aramid composite film provided by the present invention, in step S3, the preheating temperature of the smooth substrate is 70~80℃; the first direction coating speed is 0.3~0.8 m / min, the squeegee gap is 130~170µm, the post-coating treatment temperature is 75~85℃, and the treatment time is 60~120 seconds; the second direction coating speed is 0.5~1.2 m / min, and the squeegee gap is 110~150µm.
[0020] To achieve the above-mentioned objectives, the present invention also provides an application of any of the above-mentioned self-healing multifunctional aramid fiber composite films or self-healing multifunctional aramid fiber composite films prepared according to any of the above-mentioned preparation methods, applicable to any technical field such as aerospace, flexible electronics, and special protection.
[0021] Compared with the prior art, the present invention has the following technical effects: (1) It achieves efficient and reversible strong self-repair. The present invention constructs a dynamic covalent network and precisely controls the fracture and remodeling by adjusting the temperature. Under the mild conditions of 120~130℃, reversible melting-remodeling occurs, realizing molecular-level welding of the crack interface, so that the mechanical property repair efficiency is as high as 90% or more. Moreover, the process can be repeated many times, which greatly extends the service life of the material. (2) The transverse tensile strength is significantly improved. On the one hand, microscopically, the rigid main network of aramid fiber and the dynamic repair network are made to form an interpenetrating structure in space; on the other hand, macroscopically, a layered structure is formed by the rotary coating process. The layered structure makes the mechanical reinforcement phase orthogonally arranged in the two layers. This microscopic and macroscopic structure not only ensures excellent initial longitudinal and transverse mechanical properties, but also provides a stable framework and efficient stress transfer path for the repair of the dynamic network, solving the contradiction between repair and toughening. (3) Excellent comprehensive performance. While introducing self-healing function, the composite film still maintains the inherent high temperature resistance, flame retardancy and good transparency of aramid fiber due to the synergistic effect between the components, achieving a unity of multifunctionality and high performance. Detailed Implementation
[0022] The innovation of this invention lies in: (1) providing a microstructure of a composite material with "a rigid main network of aramid fiber and a dynamic covalent network of furan-maleimide interpenetrating in a bicontinuous phase", wherein the rigid main network of aramid fiber serves as the high-temperature resistant skeleton of the composite film, endowing the material with intrinsic flame retardancy, insulation and long-term service capability above 200°C, and undertaking the main load-bearing function; the dynamic covalent network of furan-maleimide Diels-Alder runs through the rigid network, and through temperature-controlled reversible covalent bond breaking and recombination, in order to generate Molecular-level welding is achieved under mild conditions of 120–130℃ for microcracks, giving the composite film efficient and repeatable self-healing capabilities. Amino-modified graphene oxide forms hydrogen bonds and chemical bonds with the matrix through its surface amino groups, and is uniformly dispersed at the interface between the two phases, effectively enhancing interlayer bonding and optimizing stress transmission paths as physical crosslinking points. Ultra-high molecular weight aramid fibers are interspersed throughout, using their long chain entanglement to improve the strength of the gel melt, suppress interlayer slippage during the coating process, and further balance the longitudinal and transverse molecular orientation, reducing anisotropy at the microscopic level. (2) The innovative "orthogonal stacked structure" is adopted. The polymer chains of the first and second layers are orthogonally aligned at 90° through the rotary coating process. This eliminates the mechanical anisotropy caused by unidirectional coating from the macroscopic structure, significantly improves the transverse tensile strength, and makes the ratio of longitudinal to transverse tensile strength close to 1. At the same time, the stacked interface can deflect and terminate the propagation of microcracks. It works in conjunction with the dynamic self-healing network to form an isotropic repair framework, ensuring that the transverse tensile strength repair efficiency is above 93% after repair and is still not less than 90% after multiple repairs. (3) The composite membrane achieves the synergistic effect of "high temperature resistance + self-healing + small difference between longitudinal and transverse tensile strength + improved transverse tensile strength", breaking through the limitation of the single function of the existing aramid composite membrane and adapting to the multi-dimensional needs of high-end scenarios.
[0023] The composite membrane of this invention comprises a continuous phase formed by a self-healing dynamic network prepolymer and a dispersed phase reinforced with amino-modified graphene oxide and ultra-high molecular weight aramid fiber. This raw material system establishes the high strength, heat resistance, and repairability of the composite membrane through chemical bonding and physical entanglement. In the preparation process, the spin coating process precisely forms a multilayered structure by controlling the coating speed and gap in orthogonal directions. The graded curing process controls solvent evaporation and crosslinking reaction kinetics through step-by-step temperature increases, matching the densification of the aramid fiber network with the in-situ formation of the dynamic covalent network. Ultimately, a self-healing multifunctional aramid fiber composite membrane with stable dual continuous phases, tight interlayer bonding, and synergistic performance is obtained.
[0024] The self-healing multifunctional aramid fiber composite membrane preparation method provided by this invention includes the following steps:
[0025] S1. Synthesis of self-healing dynamic network prepolymer: Adipic acid chloride and furanyl methylamine are reacted under alkaline conditions at 0-5℃. After precipitation and drying, furan-terminated polyamide oligomers are obtained. The furan-terminated polyamide oligomers and 4,4'-diphenylmethane bismaleimide furan groups to maleimide groups in a molar ratio of (1.02-1.10):1 are dissolved in N-methylpyrrolidone to prepare a solution with a solid content of 25wt%-35wt%. The solution is reacted at 60-70℃ for 40-60 minutes to obtain a dynamic network prepolymer solution.
[0026] S2. Preparation of the composite casting solution: Aramidized sulfone resin and ultra-high molecular weight sulfidized sulfone are dissolved in N-methylpyrrolidone to prepare a main solution with a solid content of 16wt%~20wt%. Amino-modified graphene oxide is ultrasonically dispersed in N-methylpyrrolidone to obtain a dispersion. The dispersion is added to the main solution and mixed thoroughly. Then, the dynamic network prepolymer solution prepared in step S1 is added under stirring, so that the mass ratio of prepolymer solid to sulfidized sulfone resin is (20:80)~(35:65). Solvent is added to adjust the total solid content to 18wt%~22wt%. After vacuum degassing and filtration, a uniform and stable composite casting solution is obtained. The preferred amount of amino-modified graphene oxide (NH2-GO) is 1.0 wt% of the mass of the sulfidized sulfone resin; the preferred amount of ultra-high molecular weight sulfidized sulfone is 3 wt% of the mass of the sulfidized sulfone resin.
[0027] S3. Spin coating and orthogonal stacking preparation: The casting solution is coated on a smooth substrate preheated to 70~80℃ along the first direction at a speed of 0.3~0.8m / min, with a blade gap of 130~170μm; immediately after coating, it is treated at 75~85℃ for 60~120 seconds to form the first gel layer; the substrate carrying the first gel layer is rotated 90 degrees and coated in the second direction perpendicular to the first direction at a speed of 0.5~1.2m / min, with a blade gap of 110~150μm.
[0028] S4. Graded curing and molding: The wet film is first kept at 105~115℃ for 80~100 minutes, then the temperature is gradually increased to 150~170℃ and kept for 20~40 minutes, and then the temperature is continued to be increased to 180~200℃ and kept for 20~40 minutes; after curing, it is cooled to below 60℃ and the substrate is peeled off to obtain the self-healing aramid composite film.
[0029] The longitudinal and transverse tensile strengths of the self-healing multifunctional aramid fiber composite film in this application were tested in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets"; the performance repair was determined by the ratio of the repaired transverse tensile strength to the initial transverse tensile strength, and the repair conditions were 120~130℃ and 0.1~0.5MPa pressure for 30~60 minutes; the interlaminar peel strength was tested in accordance with GB / T 8808-1988 "Peel test method for flexible composite plastic materials"; and the heat distortion temperature was tested in accordance with GB / T 1634.2-2019 "Determination of load deformation temperature of plastics - Part 2: Plastics and hard rubber".
[0030] Example 1
[0031] The amino-modified graphene oxide (NH2-GO), 4,4'-diphenylmethane bismaleimide (BMI), and N-methylpyrrolidone (NMP) used in this embodiment were all commercially available; the aramid resin (PSA) and ultra-high molecular weight aramid fiber (UHMW-PSA) were both self-made. The self-healing multifunctional aramid composite membrane was prepared according to the following steps:
[0032] S1. Synthesis of the self-healing dynamic network prepolymer. First, a furan-terminated polyamide oligomer was synthesized: adipamide chloride, hexamethylenediamine, and furanylmethylamine were added to NMP solvent in a molar ratio of 4:3:2. Triethylamine, in an equimolar amount as adipamide chloride, was added as an acid-binding agent. The mixture was stirred in an ice-water bath at 0–5°C for 4 h. After the reaction, the reaction solution was poured into deionized water to precipitate the oligomer. It was washed three times successively with deionized water and anhydrous ethanol, and then vacuum dried to obtain a white solid double-terminated furan-terminated polyamide oligomer. Then, the self-healing dynamic network prepolymer was synthesized: 5 g of the above furan-terminated polyamide oligomer and 1.74 g of BMI were dissolved together in 20.22 g of NMP to prepare a solution with a total solid content of 25 wt%. After stirring evenly, the temperature was raised to 65°C and maintained for 50 min to obtain a self-healing dynamic network prepolymer solution, wherein the molar ratio of furan groups to maleimide groups was 1.02:1.
[0033] S2. Preparation of the composite casting solution. Preparation of the main solution: Dissolve 8.00 g of aramid resin and 0.24 g of ultra-high molecular weight aramid (3 wt% of the aramid resin mass) in 33.0 g of NMP, stirring until completely dissolved to obtain a main solution with a solid content of approximately 20 wt%. Preparation of the dispersion: Add 0.08 g of NH2-GO (1.0 wt% of the aramid resin mass) to 3.0 g of NMP, and ultrasonically disperse for 30 min to obtain a uniform graphene oxide dispersion. Mixing and Solidification: The dispersion was slowly added dropwise to the main solution, and stirred at high speed for 30 min until homogeneous. Then, 8.0 g of the above dynamic network prepolymer solution (containing 2.0 g of prepolymer solids, with a prepolymer solids to aramid resin mass ratio of 20:80) was added, and stirring was continued for 20 min. NMP was added to adjust the total mass of the casting solution to 51.6 g, at which point the total solid content of the casting solution was approximately 20 wt%. After vacuum degassing and filtration through a 200-mesh filter, a homogeneous and stable composite casting solution was obtained. In this embodiment, the mass of the dynamic covalent network accounts for approximately 19.5% of the total polymer mass.
[0034] S3. Preparation of the multilayer structure by rotary coating. A clean glass plate is preheated to 75°C. An appropriate amount of casting solution is applied along the first direction (longitudinal direction) at a coating speed of 0.5 m / min and a blade gap of 150 μm. Immediately after coating, the glass plate is placed in an 80°C oven for 90 seconds to pretreat, forming a semi-dry first gel layer. The glass plate carrying the first gel layer is rotated 90 degrees, and coating is performed along the second direction (transverse direction) perpendicular to the first direction at a coating speed of 0.8 m / min and a blade gap of 130 μm, resulting in a wet film with an orthogonal multilayer structure.
[0035] S4. Graded Curing and Molding. The wet film is placed in a nitrogen-protected oven for graded curing: first, it is kept at 110℃ for 90 min to slowly remove most of the solvent; then, the temperature is gradually increased to 160℃ and kept for 30 min to further remove the solvent and allow the dynamic network to initially crosslink; finally, the temperature is increased to 190℃ and kept for 30 min to completely cure the matrix and fully crosslink the dynamic network; after curing, it is naturally cooled to below 60℃ and peeled off from the glass plate to obtain a self-healing multifunctional aramid fiber composite film with a thickness of 50±3μm.
[0036] Performance test results: longitudinal tensile strength 156MPa, transverse tensile strength 142MPa, longitudinal / transverse strength ratio 0.91; transverse strength after the first repair 134MPa, repair efficiency 94.4%; transverse strength after the fifth repair 128MPa, repair efficiency 90.1%; interlaminar peel strength 8.5 N / cm; heat distortion temperature 265℃.
[0037] Example 2
[0038] The chemicals used in this example are from the same source as in Example 1. The preparation steps are the same as in Example 1, except that: the molar ratio of furan groups to maleimide groups is 1.06:1; the mass ratio of prepolymer solid to aramid fiber is 30:70; and the solid content of the prepolymer solution is 30 wt%. The specific preparation steps are as follows:
[0039] S1. Synthesis of self-healing dynamic network prepolymer. First, furan-terminated polyamide oligomers were synthesized: exactly the same as in Example 1. Then, self-healing dynamic network prepolymers were synthesized: 5g of the above furan-terminated polyamide oligomers and 1.66g of BMI were dissolved together in 15.54g of NMP to prepare a solution with a total solid content of 30wt%; after stirring evenly, the temperature was raised to 65℃ and kept at that temperature for 50 min to obtain a dynamic network prepolymer solution, wherein the molar ratio of furan groups to maleimide groups was 1.06:1.
[0040] S2. Preparation of the composite casting solution. Preparation of the main solution: Dissolve 7.00 g of aramid resin and 0.21 g of ultra-high molecular weight aramid (3 wt% of the aramid resin mass) in 30.7 g of NMP, stirring until completely dissolved to obtain a main solution with a solid content of approximately 19.0 wt%. Preparation of the dispersion: Add 0.07 g of NH2-GO (1.0 wt% of the aramid resin mass) to 3.0 g of NMP, and ultrasonically disperse for 30 min to obtain a uniform graphene oxide dispersion. Mixing and Solidification: The dispersion was slowly added dropwise to the main solution, and stirred at high speed for 30 min until homogeneous. Then, 10.0 g of the above dynamic network prepolymer solution (containing 3.0 g of prepolymer solids, with a mass ratio of prepolymer solids to aramid resin of approximately 30:70) was added, and stirring was continued for 20 min. NMP was added to adjust the total mass of the casting solution to 51.4 g, at which point the total solid content of the casting solution was approximately 20 wt%. After vacuum degassing and filtration through a 200-mesh filter, a homogeneous and stable composite casting solution was obtained. In this embodiment, the mass of the dynamic covalent network accounted for approximately 29.4% of the total polymer mass.
[0041] S3. Spin coating to prepare the multilayer structure. The process parameters and operating steps are exactly the same as in Example 1.
[0042] S4. Graded curing and molding. The process parameters and operating steps are exactly the same as in Example 1, and the average thickness of the composite film is 51±2μm.
[0043] Performance test results: longitudinal tensile strength 149 MPa, transverse tensile strength 138 MPa, longitudinal / transverse strength ratio 0.93; transverse strength after the first repair 133 MPa, repair efficiency 96.4%; transverse strength after the fifth repair 130 MPa, repair efficiency 94.2%; interlaminar peel strength 8.2 N / cm; heat distortion temperature 260℃.
[0044] Example 3
[0045] The chemicals used in this example are from the same source as in Example 1. The preparation steps are the same as in Example 1, except that: the molar ratio of furan groups to maleimide groups is 1.1, the mass ratio of prepolymer solid to aramid fiber is 35:65, and the solid content of the prepolymer solution is 32 wt%. The specific preparation steps are as follows:
[0046] S1. Synthesis of self-healing dynamic network prepolymer. First, furan-terminated polyamide oligomers were synthesized: exactly the same as in Example 1. Then, self-healing dynamic network prepolymers were synthesized: 5g of the above furan-terminated polyamide oligomers and 1.59g of BMI were dissolved together in 14.02g of NMP to prepare a solution with a total solid content of 32wt%; after stirring evenly, the temperature was raised to 65℃ and the reaction was maintained for 50 min to obtain a dynamic network prepolymer solution, wherein the molar ratio of furan groups to maleimide groups was 1.10:1.
[0047] S2. Preparation of the composite casting solution. Preparation of the main solution: Dissolve 6.50 g of aramid resin and 0.195 g of ultra-high molecular weight aramid (3 wt% of the aramid resin mass) in 28.5 g of NMP, stirring until completely dissolved to obtain a main solution with a solid content of approximately 19.0 wt%. Preparation of the dispersion: Add 0.065 g of NH2-GO (1.0 wt% of the aramid resin mass) to 3.0 g of NMP, and ultrasonically disperse for 30 min to obtain a uniform graphene oxide dispersion. Mixing and Solidification: The dispersion was slowly added dropwise to the main solution, and stirred at high speed for 30 min until homogeneous. Then, 10.94 g of the above dynamic network prepolymer solution (containing 3.5 g of prepolymer solids, with a mass ratio of prepolymer solids to aramid resin of approximately 35:65) was added, and stirring was continued for 20 min. NMP was added to adjust the total mass of the casting solution to 51.3 g, at which point the total solid content of the casting solution was approximately 20 wt%. After vacuum degassing and filtration through a 200-mesh filter, a homogeneous and stable composite casting solution was obtained. In this embodiment, the mass of the dynamic covalent network accounts for approximately 34.3% of the total polymer mass.
[0048] S3. Preparation of multilayer structure by rotary coating: The process parameters and operation steps are exactly the same as in Example 1.
[0049] S4. Graded curing and molding. The process parameters and operating steps are exactly the same as in Example 1, and the average thickness of the composite film is 52±3μm.
[0050] Performance test results: longitudinal tensile strength 140MPa, transverse tensile strength 130MPa, longitudinal / transverse strength ratio 0.93; transverse strength after the first repair 127MPa, repair efficiency 97.7%; transverse strength after the fifth repair 125MPa, repair efficiency 96.2%; interlaminar peel strength 7.9 N / cm; heat distortion temperature 256℃.
[0051] Comparative Example 1 (unidirectional single-coat, no orthogonal layer structure)
[0052] The main difference from Example 1 is that the rotational orthogonal coating process is omitted, and a single-pass unidirectional coating is used to form the film. All other raw material ratios, pre-gelling, and graded curing processes are completely consistent with Example 1. By adjusting the blade gap to 280 μm, the final film thickness is ensured to be comparable to that of Example 1.
[0053] Preparation method: The casting solution was prepared in exactly the same way as in Example 1; the casting solution was applied to a glass plate preheated to 75°C in a single direction with a blade gap of 280 μm; after application, the film was pretreated at 80°C for 90 s to form a gel layer; the subsequent graded curing process was exactly the same as in Example 1, and the film was peeled off after cooling to obtain a unidirectional coated composite film.
[0054] Performance test results: longitudinal tensile strength 162 MPa, transverse tensile strength 97 MPa, longitudinal / transverse strength ratio 0.60; transverse strength after the first repair 91 MPa, repair efficiency 93.8%; strength after the fifth repair 83 MPa, repair efficiency 85.6%.
[0055] Experimental conclusion: Compared with Example 1, the longitudinal strength was slightly improved, but the transverse strength decreased, and the difference between the longitudinal and transverse strengths was significant; this proves that the orthogonal laminated structure is the core means to solve the mechanical anisotropy of aramid fiber film and significantly improve the transverse strength.
[0056] Comparative Example 2 (Furan-maleimide-free dynamic covalent network)
[0057] The main difference from Example 1 is that no self-healing dynamic network prepolymer is added. The corresponding mass is made up with ordinary aramid resin, and the remaining components, orthogonal coating, and curing process are completely consistent with Example 1.
[0058] Preparation method: Dissolve 10.00g of aramid resin and 0.30g of ultra-high molecular weight aramid in NMP to prepare a main solution; add 0.10g of NH2-GO dispersion and add NMP to adjust the total solid content to 20 wt%; after degassing and filtration, prepare a film using the same orthogonal coating and graded curing process as in Example 1.
[0059] Performance test results: longitudinal tensile strength 153 MPa, transverse tensile strength 136 MPa, longitudinal / transverse strength ratio 0.89; transverse strength after the first repair 37 MPa, repair efficiency 27.2%; strength after the fifth repair 19 MPa, repair efficiency 14.0%; interlaminar peel strength 6.3 N / cm.
[0060] Experimental conclusion: Compared with Example 1, the initial mechanical properties are similar, but the self-healing efficiency is reduced, and the repair ability is almost lost after multiple repairs; this proves that the furan-maleimide Diels-Alder dynamic covalent network is the core functional phase for achieving efficient and reversible self-healing.
[0061] Comparative Example 3 (without the addition of ultra-high molecular weight aramid fiber)
[0062] The difference from Example 1 is that the ultra-high molecular weight aramid fiber component was removed. The corresponding mass was made up with ordinary aramid fiber resin, while the remaining components, proportions, coating and curing processes were completely consistent with Example 1.
[0063] Preparation method: 8.24 g of aramid resin was dissolved in NMP to prepare a main solution; 0.08 g of NH2-GO dispersion and a dynamic prepolymer solution containing 2.00 g of solids were added, and NMP was added to adjust the total solid content to 20 wt%. The subsequent orthogonal coating and graded curing processes were completely consistent with those in Example 1.
[0064] Performance test results: longitudinal tensile strength 139MPa, transverse tensile strength 125MPa, longitudinal / transverse strength ratio 0.90; transverse strength after the first repair 113MPa, repair efficiency 90.4%; strength after the 5th repair 102MPa, repair efficiency 81.6%; interlaminar peel strength 5.1N / cm.
[0065] Experimental conclusions: Compared with Example 1, the initial longitudinal and transverse strength decreased, the interlayer peel strength decreased, and the performance degradation intensified after multiple repairs; this proves that ultra-high molecular weight aramid fiber can strengthen the cohesive force and interlayer bonding force of the matrix through long chain entanglement, while improving mechanical strength and repair stability.
[0066] Comparative Example 4 (without amino-modified graphene oxide)
[0067] The difference from Example 1 is that the amino-modified graphene oxide component is removed. All other raw materials, proportions, and processes are completely consistent with Example 1.
[0068] Preparation method: 8.00g of aramid resin and 0.24g of ultra-high molecular weight aramid were dissolved in NMP to prepare a main solution. A dynamic prepolymer solution containing 2.00g of solids was added, and NMP was added to adjust the total solids content to 20 wt%. The subsequent orthogonal coating and graded curing processes were completely consistent with those in Example 1.
[0069] Performance test results: longitudinal tensile strength 141 MPa, transverse tensile strength 127 MPa, longitudinal / transverse strength ratio 0.90; transverse strength after the first repair 112 MPa, repair efficiency 88.2%; strength after the fifth repair 101 MPa, repair efficiency 79.5%; heat distortion temperature 248℃.
[0070] Experimental conclusions: Compared with Example 1, the initial strength decreased, the self-healing efficiency decreased, and the heat distortion temperature decreased; this proves that amino-modified graphene oxide can improve the compatibility between the two phases through interfacial bonding, and simultaneously achieve mechanical enhancement, thermal stability improvement and repair efficiency optimization.
Claims
1. A self-healing multifunctional aramid fiber composite membrane, characterized in that... The composite membrane is formed by a spin coating process using a composite casting solution prepared from aramid resin dissolved or dispersed in N-methylpyrrolidone, ultra-high molecular weight aramid, amino-modified graphene oxide, and a self-healing dynamic network prepolymer to form an orthogonal stacked structure. The composite membrane comprises a bicontinuous phase formed by the self-healing dynamic network prepolymer and the rigid aramid main network, and a dispersed phase reinforced with amino-modified graphene oxide and ultra-high molecular weight aramid. The composite membrane has a longitudinal-to-transverse strength ratio ≥0.91, an interlayer peel strength ≥7.9 N / cm, and a transverse tensile strength recovery rate ≥93% after the first repair.
2. The self-healing multifunctional aramid fiber composite membrane as described in claim 1, characterized in that... In the dual continuous phase, the rigid aramid main network serves as the high-temperature resistant skeleton of the composite membrane and undertakes the main load-bearing function; the self-healing dynamic network prepolymer is a furan-maleimide dynamic covalent network, which runs through the rigid aramid main network. Through temperature-controlled reversible covalent bond breaking and recombination, the composite membrane is endowed with self-healing ability: the composite membrane repair process can be repeated at least 5 times, and the transverse tensile strength recovery rate after the 5th repair is not less than 90%.
3. The self-healing multifunctional aramid fiber composite membrane as described in claim 1, characterized in that... The self-healing dynamic network prepolymer is prepared by reacting furan-terminated polyamide with 4,4'-diphenylmethane bismaleimide in a molar ratio of furan group to maleimide group of (1.02~1.10):1; the mass ratio of the self-healing dynamic network prepolymer to the aramid resin is (20:80)~(35:65).
4. A method for preparing a self-healing multifunctional aramid fiber composite membrane as described in any one of claims 1 to 3, characterized in that, Including the following steps: S1. Synthesis of self-healing dynamic network prepolymer: First, furan-terminated polyamide oligomers are synthesized; then, furan-terminated polyamide oligomers and 4,4'-diphenylmethane bismaleimide are dissolved in N-methylpyrrolidone to prepare a solution with a solid content of 25 wt%~35 wt%, and the self-healing dynamic network prepolymer solution is obtained after the reaction. S2. Preparation of composite casting solution: Aramid sulfone resin and ultra-high molecular weight aramid sulfone are dissolved in N-methylpyrrolidone to prepare a main solution with a solid content of 16wt%~20wt%; amino-modified graphene oxide is ultrasonically dispersed in N-methylpyrrolidone to obtain a dispersion; the dispersion and the main solution are mixed evenly and then added to the dynamic network prepolymer solution obtained in step S1. Solvent is added to adjust the total solid content. After vacuum degassing and filtration, a uniform and stable composite casting solution is obtained. S3. Spin coating to prepare a multilayer structure: The casting solution is coated along the first direction on a preheated smooth substrate to obtain the first gel layer. Rotate the substrate carrying the first gel layer by 90 degrees and perform a second direction coating along a direction perpendicular to the first direction to obtain a wet film with a stacked structure. S4. Graded curing and molding: Under inert gas protection, the wet film is first kept at 105~115℃ for 80~100 minutes; then the temperature is gradually increased to 150~170℃ and kept for 20~40 minutes; then the temperature is further increased to 180~200℃ and kept for 20~40 minutes; after curing, the substrate is cooled and peeled off to obtain the self-healing multifunctional aramid composite film.
5. The method for preparing a self-healing multifunctional aramid fiber composite membrane as described in claim 4, characterized in that, In step S1, the furan-terminated polyamide oligomer and the 4,4'-diphenylmethane bismaleimide amine furan group to maleimide group are prepared in a molar ratio of (1.02~1.10):
1.
6. The method for preparing a self-healing multifunctional aramid fiber composite membrane as described in claim 5, characterized in that, In step S1, the synthesis of the furan-terminated polyamide oligomer includes the following steps: (1) Add adipic acid chloride, hexamethylenediamine and furanylmethylamine to NMP solvent in a molar ratio of 4:3:2, and add triethylamine in an equal molar amount to adipic acid chloride as an acid-binding agent. Stir the reaction under ice-water bath conditions of 0~5℃. (2) After the reaction is complete, the reaction solution is poured into deionized water to precipitate, and then washed with deionized water and anhydrous ethanol in sequence. After vacuum drying, the product is obtained.
7. The method for preparing a self-healing multifunctional aramid fiber composite membrane as described in claim 4, characterized in that, In step S1, the self-healing dynamic network prepolymer reaction is a solution with a solid content of 25%~35% reacting at 60~70°C for 40~60 minutes.
8. The method for preparing a self-healing multifunctional aramid fiber composite membrane as described in claim 4, characterized in that, The mass ratio of the self-healing dynamic network prepolymer solid to the aramid resin in the composite casting solution is (20:80) to (35:65).
9. The method for preparing a self-healing multifunctional aramid fiber composite membrane as described in claim 4, characterized in that, In step S3, the preheating temperature of the smooth substrate is 70~80℃; the first direction squeegee speed is 0.3~0.8 m / min, the squeegee gap is 130~170µm, the post-squeegee treatment temperature is 75~85℃, and the treatment time is 60~120 seconds; the second direction squeegee speed is 0.5~1.2 m / min, and the squeegee gap is 110~150µm.
10. The application of any of the self-healing multifunctional aramid fiber composite films according to claims 1-2 or prepared by any of the preparation methods according to claims 3-9, characterized in that, It is applicable to any technical field, including aerospace, flexible electronics, and special protection.